Gene Editing to Tackle Facioscapulohumeral Muscular Dystrophy - Mariot, Virginie; Dumonceaux, Julie (Frontiers in Genome Editing, 2022)
Facioscapulohumeral dystrophy (FSHD) is a skeletal muscle disease caused by the aberrant expression of the DUX4 gene in the muscle tissue. To date, different therapeutic approaches have been proposed, targeting DUX4 at the DNA, RNA or protein levels. The recent development of the clustered regularly interspaced short-palindromic repeat (CRISPR) based technology opened new avenues of research, and FSHD is no exception. For the first time, a cure for genetic muscular diseases can be considered. Here, we describe CRISPR-based strategies that are currently being investigated for FSHD. The different approaches include the epigenome editing targeting the DUX4 gene and its promoter, gene editing targeting the polyadenylation of DUX4 using TALEN, CRISPR/Cas9 or adenine base editing and the CRISPR-Cas9 genome editing for SMCHD1. We also discuss challenges facing the development of these gene editing based therapeutics.